2019
DOI: 10.21203/rs.2.15337/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Persistent domestic circulation of African swine fever virus in Tanzania, 2010-2017

Abstract: Background African swine fever (ASF) is a highly fatal viral hemorrhagic disease of domestic pigs that threatens livelihoods and food security. In Africa, ASF virus (ASFV) circulates in sylvatic (transmission between warthogs and soft argasid ticks) and domestic (transmission between domestic pigs) cycles, with outbreaks resulting from viral spill-over from sylvatic cycle. The present study investigated ASFV transmission patterns through virus genotyping. Results Genotypes II, IX, X, XV and XVI of ASFV were fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In addition, homology between ASFV strains from ticks collected at pig shelters and those from warthog burrows was observed, suggesting the possibility of ASFV transmission at the wild and domestic pigs interface [20]. Among countries included in this review, the ASFV p72 genotype II was described in Zambia [17,40], Mozambique [20,22,49], Tanzania [56,59,62], and in Malawi [63]. In 2007, the ASFV p72 genotype II escaped from its African geographical distribution to Georgia and subsequently spread to countries of the European Union and Russia before it reached Asia in August 2018 [13,25].…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…In addition, homology between ASFV strains from ticks collected at pig shelters and those from warthog burrows was observed, suggesting the possibility of ASFV transmission at the wild and domestic pigs interface [20]. Among countries included in this review, the ASFV p72 genotype II was described in Zambia [17,40], Mozambique [20,22,49], Tanzania [56,59,62], and in Malawi [63]. In 2007, the ASFV p72 genotype II escaped from its African geographical distribution to Georgia and subsequently spread to countries of the European Union and Russia before it reached Asia in August 2018 [13,25].…”
Section: Discussionmentioning
confidence: 91%
“…The genotype X was recovered from domestic pigs in 1950 in Kenya [15], since then, it was regularly reported to circulate and cause ASF outbreaks in Kenya [15,16,21,23], Uganda [21,23], Tanzania [22,23,61,62], Burundi [22,23,64], and DRC [51]. Recent molecular studies have reported high genetic similarity at three genomic regions of ASFV (p72, CVR and I73R-I329L) between the ASFV p72 genotype X strains responsible for ASF outbreaks in 2016 in Kagera region in Tanzania [62,64], the 2018 ASF outbreak in Rutana region in Burundi [64], and the ASF outbreak that occurred during December 2018 to January 2019 in South Kivu province of the DRC [51]. Commercial traffic and cross-border movements of domestic pigs and pork products were speculated as the main drivers of the ASFV spread between DRC, Burundi, and Tanzania [51,53,64].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations